Diagnostic Value of Plain Chest Roentgenogram in Rheumatic Mitral Valvular Disease - Bambang Madiyono; Indra Sugiarno; Sukman T. Putra; Sudigdo Sastroasmoro; Widhodho T. Karyomanggolo; Hariarti S. Pramulyo (Paediatrica Indonesiana, 1996)
Rheumatic fever and rheumatic heart disease are still important community health problem in developing countries. The aim of this diagnostic test was to determine the diagnostic role of plain chest roentgenogram in patients with rheumatic mitral valvular disease. Subjects were patients with rheumatic mitral disease without other valvular lesions, congenital heart disease, or anemia, who visited the out-patient clinic, Department of Child Health, Cipto Mangunkusumo Hospital, Jakarta, between June and August 1995. There were 52 subjects enrolled to this study. Determination of type valve lesions, the presence of left atrial dilatation, and cardio-thoracic ratio (CTR) were performed from plain chest film by 2 pediatric radiologists using a semiquantitative table. The results were compared with échocardiographie findings used as gold standard. The chest plain roentgenogram accuracy in determining valvular lesion was 77% (090%; 67.4%-86.6%). Chest plain roetgenogram diagnostic index in discovering left atrial dilatation gave excellent result (>80%). The correlation between CTR and left ventricular mass (LVM) was 0,63 (p<0.001) in all rheumatic mitral valvular lesions. We conclude that plain chest roentgenogram still has its place in determining type of rheumatic mitral valvular lesion, and it has some help in the management of patients with rheumatic mitral valve disease.